Linux basics for hackers : getting started with networking, scripting, and security in Kali - OccupyTheWeb (No Starch Press, 2019)
If you're getting started along the exciting path of hacking, cybersecurity, and pentesting, this practical, tutorial-style book uses the Kali Linux distribution to teach Linux basics with a focus on how hackers would use them. --